Lexical bundles in learner language: Lithuanian learners vs. native speakers - Juknevičienė, Rita (Kalbotyra, 2009)
Corpus studies of recurrent word sequences, also known as lexical bundles, have outlined new directions in ELT/EFL research. The fact that naturally produced English consists of prefabricated multi-word units gave rise to the question of chunkiness in learner language. This study was thus designed to compare and contrast language produced by learners of three different levels of proficiency in terms of the use of lexical bundles. The analysis of lexical bundles retrieved from three corpora of written learner English showed that many more different bundles were established in the corpora representing less proficient learners which is interpreted as an indication of a more limited lexical repertoire which leads to more repetition. Furthermore, structural and functional analysis of lexical bundles showed that the language of non-native learners bears more resemblance to spoken English than the language of native speakers. These findings may be particularly useful to EFL practitioners as they seem to give new insights into the development of learner language.